Impact of Ownership Structure and Corporate Governance on Earning Management: Empirical Findings from Listed Firms on the Pakistan Stock Exchange - Bashir, Babar; Rashid, Muhammad; Bashir, Zeeshan (SEISENSE Journal of Management, 2024)
Purpose- This study investigates the interplay among Ownership Structure, Corporate Governance, and Earnings Management by employing ordinary least square (OLS) regression. To find the relationship among the three constructs based on data sourced from listed companies on the Pakistan Stock Exchange spanning 2016-2021 were used, excluding the financial industry due to its unique reporting system.Design/Methodology- The sample comprises 111 firms chosen based on data availability. To measure earnings management, the researchers used a modified version of John's model (1995) to estimate discretionary accruals. Findings- The study's key findings include the significant role of institutional investors in reducing earnings management. The number of board directors and ownership concentration were observed to impact discretionary accruals. Control variables indicated that more profitable, growing, and highly leveraged firms tend to engage in earnings management, which decreases with the firm's age. The study revealed a diverse relationship between ownership structure, corporate governance codes, and earnings management. Notably, significant institutional investment reduces ownership concentration, leading to decreased earnings management. Moreover, the results show a positive and significant correlation between firm size and Return on Assets (ROA). Practical Implications- Board independence was found to have a positive impact on earnings management, suggesting that boards serve a more complex role than mere monitoring to mitigate accounting manipulation.